Autism spectrum disorder is associated with gut microbiota disorder in children - Sun, Hairong (BMC Pediatr, 2019)
BACKGROUND: The aim of this study was to evaluate the occurrence and clinical characteristics of autism spectrum disorder (ASD) associated to the stable state of the gut microbiota. METHODS: A total of 9 children with ASD and 6 healthy children used as control were selected and feces samples were collected from all of them. The 16S gene ribosomal RNA sequencing was used to analyze the difference in gut microbiota between healthy control children and ASD patients. RESULTS: The results of 16S sequencing based on operational taxonomic units (OTUs) analysis showed that the ASD group and the healthy control (HC) group had a large difference in the abundance of microbiota at the level of family, genus and species. The abundance of Bacteroidales and Selenomonadales was significantly lower in the ASD group than in the HC group (p = 0.0110 and p = 0.0076, respectively). The abundance of Ruminococcaceae in the ASD group was higher than that in the HC group (p = 0.0285), while the amount of Prevotellaceae was significantly lower in the ASD group than in the HC group (p = 0.0111). The Tax4Fun analysis based on Kyoto Encyclopaedia of Genes and Genomes (KEGG) data indicated differentially expressed functional pathway between the ASD group and healthy control group associated to the nervous system, environmental information processing and cellular processing. CONCLUSIONS: The abundance of gut microbiota in the ASD group is different from that in the healthy control children. These differences affect the biological function of the host. These results suggest that a disorder in the gut microbiota may be associated, at least in part, with ASD in children.